Perkawinan Sah ke Dua tanpa Penetapan Poligami - Nur Wahyu Illahi (Warmadewa Press, 2024)
Human needs are diverse, and to fulfill these needs, humans will exert all their efforts and strength through intellect and actions. However, these efforts often do not align and frequently lead to controversies in various aspects, especially in conflicts of law. Polygamy, for instance, has been a persistent issue from the past until now. Structured polygamy does not cause problems, but when polygamy involves falsification of identity, it can create significant issues. For example, in the Surabaya District Court ruling No. 1459/Pid.B/2021/PN Sby, it was a case of polygamy without court approval, resulting in two valid marriage certificates. The main issue here is the implication for the Office of Religious Affairs if there are valid certificates in different cities or districts. The aim of this research is to address problems related to marriage law in administrative terms. Considering the existence of administrative or procedural aspects is very inherent in Indonesia. This research uses three approaches: statute, conceptual, and case. The analytical technique used is from general to specific, known as the deductive method, resulting in descriptive analysis. The results of the study show that if the Office of Religious Affairs commits negligence, there are administrative sanctions categorized as minor.